Identifying and Characterizing Novel Antithrombin-Inhibiting RNA Aptamers - Hamada, Mostafa (My University, 2022)
Antithrombin (AT) is a plasma serine protease inhibitor that regulates thrombin and other activated clotting factors in the intrinsic and common pathways of coagulation. As the most abundant coagulation pathway inhibitor, AT serves to maintain balance in the coagulation system by inducing an anticoagulant effect. The importance of AT is evident in cases where deficiencies of AT lead to increased risk of venous thromboembolic disease. Since an AT antagonist would be considered a procoagulant, inactivating AT could provide a novel approach to restoring hemostasis in patients with inherited or acquired bleeding disorders. In vitro selection is a powerful tool used to screen large combinatorial oligonucleotide libraries against a target molecule or protein. By employing this technique in combination with high-throughput screening, we identified novel RNA aptamer candidates capable of binding AT with high affinity and inhibiting AT’s inactivation of its main target protease, thrombin. Kinetic characterization of the most abundant aptamer candidates showed a reduction in AT-mediated thrombin inhibition of 50-60%. The most inhibitory aptamer, R6_15, mediated a decrease of AT’s second-order rate constant from 2.37 ± 0.06 x 104 to 1.57 ± 0.02 x 104 M-1 s-1 (mean ± SD) The interaction between the aptamers and AT was also measured in human plasma. In a clotting assay, aptamer R6_15 accelerated clotting time by approximately 7 seconds (from 44.3 ± 0.8 to 37.3 ± 0.7 seconds). This difference in clotting time was the greatest noticed among all the other aptamer candidates. By measuring the change in AT’s fluorescence intensity, we were able to determine the aptamers’ binding capacity. The binding affinities (kd) of aptamers R6_15 and R6_19 were 65.3 ± 8.7 and 67.5 ± 14.5 nM, respectively. Truncation of R6_15 on either its 5’ or 3’ end did not increase its inhibitory activity or binding affinity towards AT. By pairing the selection data with dynamic molecular modelling, the interface of aptamer R6_15 to AT was predicted to be at the site of heparin binding, specifically at residue K114. Although these computer-generated results are not conclusive, they provide a testable hypothesis for future experimentation. Ultimately, this work provides evidence that the application of in vitro evolution has yielded a novel anti-serpin aptamer. With some modifications, the selection protocol employed in this study could be revisited to identify tighter binders and more potent inhibitors of AT. Either aptamer R6_15 or a future higher affinity AT-binding aptamer could be tested for its efficacy in reducing bleeding in vivo using mouse models of acquired hemophilia or traumatic bleeding.
Keywords: aptamers; antithrombin